Digital Technologies in L2 teaching-learning in Brazil: A Critical Content Analysis - Leão, Roberta Gomes; Finardi, Kyria Rebeca (Education and Linguistics Research, 2024)
The aim of this study is to reflect about the view of digital technologies in L2 teaching-learning. With that aim, a content analysis study was carried out in the Brazilian database of theses and dissertations defended between 2015 and 2019 to analyze the view of technologies in the area of L2 teaching-learning. Drawing on the Critical Theory concept of semiformation and content analysis techniques, the view/use of technologies in L2 teaching-learning was analyzed in the corpus of 22 works. Results suggest challenges in the advancement of research and critical use of technologies in L2 teaching-learning in Brazil once few studies promoted a reflexive dialogue with the participants in order make them think about the critical use of technologies in L2 teaching-learning. The study concludes with the suggestion for more investment in the human formation process through the critical use of technologies in the teaching-learning of L2.